Fixed Point Theorems in Cone Banach Spaces - Karapınar Erdal (Fixed Point Theory and Applications, 2009)
In this manuscript, a class of self-mappings on cone Banach spaces which have at least one fixed point is considered. More precisely, for a closed and convex subset of a cone Banach space with the norm , if there exist , , and satisfies the conditions and for all , then has at least one Fixed point.